Razvojne faze i procesi disperzije industrije Zagreba - Feletar, Dragutin (Array, 1990)
The author studies the main development phases of the Zagreb industry in the past 150 years dividing them into four periods (1) Manufactural phase, (2) Railway phase, 1862-1918, and (4) Post-war phase or the phase of contemporary development of the Zagreb industry, 1945-1990. The last phase is characterized by the highest growth of the Zagreb industry and is divided into four subphases: (a) centralistic, (b) extensive investment, (c) import dependent development, and (d) stabilization. The second part of the paper deals with the recent dispersion of industrial plants outside the town of Zagreb.